The effect of different vertical zinc distribution on the early root development and zinc accumulation of Brassica napus - Feigl Gábor; Molnár Árpád; Krajner Jolán; Oláh Dóra; Kolbert Zsuzsanna; International Symposium on Analytical and Environmental Problems (24.) (2018) (Szeged) (2018)
The early development of the root system is highly important for the plants’ whole life; it is regulated by a complex system which integrates endogenous and environmental signals. Heavy metals (HMs) as exogenous factors have a different, concentration-dependent effect on the developing root: low concentrations cause stress-induced morphogenic response (SIMR, adaptation mechanism, more branched, shallower roots), while higher concentrations inhibit growth. Plants encounter heavy metals in many different ways, not only the widely studied homogenous distribution. Thus investigation of the effect of vertical distribution of HMs on the root development of crops has a great importance. In our experiments, to be able to determine and characterise the exact effect of excess zinc (Zn) on the root growth of Brassica napus L., several different layouts were used in soil-filled rhizotrons. This setup allowed us to examine the root growth of rapeseed in a practically 2D system, submitted to heterogeneously layered Zn-contaminated soil.